Design and analysis of smoke flow visualization apparatus for wind tunnel. Issue 1 (November 2021) - Raval, D; Jain, S V; Acharii, A M; Ghosh, K
Abstract: In the present study, the design and analysis of smoke generator are done for the low-speed wind tunnel. The wind tunnel fan is fitted with the Variable Frequency Drive to produce the wind speed in the range of 3 to 32 m/s with fan speed of 150 to 1500 rpm. The design of smoke generator was done according to Preston Sweeting mist generator principle corresponding to the free stream velocity of 3 m/s. A controlled smoke generator consisting of kerosene reservoir, controlled heater, blower, liquid column height adjustment mechanism, valves etc. was designed and fabricated. The smoke generator produced the smoke at the rate of 154 cm 3 /s which was close to the design flow rate of 149 cm 3 /s. To supply the required quantity of smoke in the wind tunnel, the smoke rake of NACA 0010 profile was developed and installed in the rapid contraction section of the wind tunnel to achieve the streamlined flow. The parametric studies were done on the smoke generator at different power inputs and its effects were studied on smoke temperature, smoke discharge and boiling time of the kerosene. The flow visualization was carried out on NACA 0015 airfoil model and the images were captured to examine the flow physics around them under different operating conditions.